Introduction: the challenge of adaptive collaborative management - Schelhas, J.; Buck, L.; Geisler, C.C. (CRC Press, 2001)
Efforts to link conservation and development have met with substantial challenge. Although integrated conservation and development projects (ICDPs) raised hopes that "win-win" outcomes were possible, experience has shown the many difficulties of protecting international and local agendas for conservation of biological diversity where livelihood goals were also important. Adaptive collaborative management (ACM) may be one approach that better balances local, national and global interests in conserving biodiversity with competing interests for resource use. This chapter provides an introduction to the state of the art of ACM as an approach for protected area management.